Land cover transitions in the United States South: 2007–2013. (April 2019) - Bettinger, Pete; Merry, Krista
Abstract: The southern United States (the South) has been managed extensively by humans since the onset of European colonization in the 1600s. The study represents a change detection analysis where the locations of 15, 000 image sample points were distributed randomly across 12 southern states, and Google Earth imagery for the years 2007–2013 was consulted to determine which of 13 major land classes and associated subclasses were evident at these points. Standard image interpretation principles were employed, approximately 15% of the sample points were re-examined during the survey, and approximately 4.4% of the sample points were examined as part of an accuracy assessment after the survey was conducted. In addition to an assessment of land area occupied by the 13 major land classes and their subclasses, confidence intervals for these estimates were developed, and annual rates of management activity were estimated. Increases in the human living and commerce space of the southern landscape were observed to be mainly at the expense of tree covered ecosystems (generally exclusive of woodlands in Texas and Oklahoma), cropland, and pasture areas. Developed areas represented nearly 1.5% of the South in 2013, and transportation areas represented about 1.6%. Each gained land from the other land use classes over the study period. Estimates of tree cover, about 42%, were consistent with previous reports that estimated it to range from about 41 to 46% over the last six decades. Short-term general transitions associated with the tree cover, cropland, pasture and grass areas illustrated the dynamic nature of the surface of the earth in the South, mainly as influenced by opportunistic human activity. For example, expansion of developed areas through new homes, driveways, parking lots, sidewalks, and other built features are likely due to decisions made at the local level by an expanding human population without reference to a broader coordinated plan. Highlights: Land use class assessment in the southeastern United States using Google Earth imagery across multiple years. Decline in tree cover between 2007 and 2013. Increase in developed area to around 1.5% of the South.